Solid organ transplant–specific antibiogram in a tertiary pediatric hospital in Canada. (2nd February 2021) - Kitano, Taito; Science, Michelle; Nalli, Nadya; Timberlake, Kathryn; Allen, Upton; Teoh, Chia Wei; Campigotto, Aaron
Abstract: SOT recipients are more vulnerable to infections with antimicrobial‐resistant organisms, and therefore, it may be useful for transplant centers to create transplant‐specific antibiograms to direct empirical antimicrobial regimens and monitor trends in antimicrobial resistance. SOT‐specific antibiograms were created using antimicrobial susceptibility data on isolates from 2012 to 2018 at The Hospital for Sick Children, Toronto, Ontario, Canada. The CLSI guidelines were followed to generate the antibiograms except that results from 2 years of data were pooled on a rolling basis to achieve larger sample sizes. The 3 most frequent organisms in one analysis period of the SOT antibiogram were Escherichia coli (average sample size ±standard deviation; n = 28.7 ± 3.8), Staphylococcus aureus (n = 27.8 ± 5.0), and Pseudomonas aeruginosa (non‐CF) (n = 19.8 ± 8.8). For E.coli, susceptibilities in the SOT antibiogram were significantly lower than those in the hospital‐wide antibiogram in 2017–2018 for ampicillin (27% vs 47%; p = .014), piperacillin/tazobactam (55% vs 88%; p < .001), cefotaxime (59% vs 89%; p < .001), ciprofloxacin (71% vs 88%; p = .007), and trimethoprim‐sulfamethoxazole (41% vs 69%; p = .001), but not significantly different for aminoglycosides and meropenem. In the SOT antibiogram of E . coli, decreased susceptibility trend was confirmed in some antibiotics, including piperacillin/tazobactam (83% in 2012–2013 vs 55% in 2017–2018). At our center, the solid organ transplant–specific antibiogram revealed important differences in E . coli susceptibilities and trends in antimicrobial resistance. Developing a SOT antibiogram will assist in revising and improving empiric treatment guidelines as well as monitoring antimicrobial resistance in this population.